Funding Charter Schools: A Safe Bet? An Analysis of Rhode Island's Charter School Investments - Carreno, Mario (My University, 2024)
There are two major theories that scholars utilize and debate in the study of public education in the United States. The first theory is centered on the notion that existing school districts should be supported with additional funding and resources to improve student outcomes. This theory argues that additional resources allow traditional districts to better serve students by providing specialized teachers, additional teachers’ aides, and other supplemental supports that benefit all students in the district. Conversely, proponents of charter schools argue that school choice — creating an educational market — incites competition between Local Education Agencies for both students and funding. This competition is achieved through the creation of public charter schools, which compete with traditional districts. This research focuses on the State of Rhode Island’s educational funding, using publicly available longitudinal empirical data between Fiscal Years 2010 and 2019. Through the lenses of equity, efficiency and effectiveness, this research analyzes the State’s return-on-investment of charter schools. The data suggest that Rhode Island charter schools disproportionately under-enroll disadvantaged students (i.e., special education, English language learners, and free and reduced lunch eligible) as compared to their sending districts and divert hundreds of millions of dollars in funding from traditional districts. However, the study does not find that this adversely impacts the sending district’s average scale scores on the Rhode Island Comprehensive Assessment System (RICAS) or the Scholastic Assessment Test (SAT).
Keywords: Dissertations, Academic--United States; Public administration; Education—Finance; Charter schools—United States; School choice—United States; Educational equalization—United States